MinD2 modulates cell shape and motility in the archaeon Haloferax volcanii - Patro, Megha; Grünberger, Felix; Sivabalasarma, Shamphavi; Gfrerer, Sabrina; Rodriguez-Franco, Marta; Nußbaum, Phillip; Grohmann, Dina; Ithurbide, Solenne; Albers, Sonja-Verena (Frontiers in Microbiology, 2024)
In bacteria and archaea, proteins of the ParA/MinD family of ATPases regulate the spatiotemporal organization of various cellular cargoes, including cell division proteins, motility structures, chemotaxis systems, and chromosomes. In bacteria, such as Escherichia coli, MinD proteins are crucial for the correct placement of the Z-ring at mid-cell during cell division. However, previous studies have shown that none of the 4 MinD homologs present in the archaeon Haloferax volcanii have a role in cell division, suggesting that these proteins regulate different cellular processes in haloarchaea. Here, we show that while deletion of MinD2 in H. volcanii (∆minD2) does not affect cell growth or division, it impacts cell shape and motility by mispositioning the chemotaxis arrays and archaellum motors. Finally, we explore the links between MinD2 and MinD4, which has been previously shown to modulate the localization of chemosensory arrays and archaella in H. volcanii, finding that the two MinD homologues have synergistic effects in regulating the positioning of the motility machinery. Collectively, our findings identify MinD2 as an important link between cell shape and motility in H. volcanii and further our understanding of the mechanisms by which multiple MinD proteins regulate cellular functions in haloarchaea.